Enhancement of dry reforming of methane for syngas production over M/Mg1-XM’xO catalysts (M=Ni, Pd, and Pt., M’=Ce3+, Ce4+, and Ni2+) - Jassim Aldoghachi, Faris Abdulridha (2016)
In this study, the conversion of methane and carbon dioxide to synthesis gas using dry reforming of methane over Ni, Pd, and Pt/MgO catalysts in different concentrations of Ce3+, Ce4+and Ni2+ was prepared via the co-precipitation of Mg and Ce nitrates, followed by impregnation with 1 wt.% each of Ni, Pd, and Pt metals to form Pt/Mg1- xNixO, Pd/Mg1-xCe3+ xO, Pd/Mg1-xCe4+ xO and Ni,Pd,Pt/Mg1-xCexO catalysts. The goal of this study was to prepare a catalyst with high activity and selectivity which prevent the carbon deposition onto the catalyst during the syngas production. The performance of metal / magnesia-promoter catalysts in syngas production and the factors influencing carbon deposition during reaction were also investigated. The produced catalysts were characterized using various kinds of analytical techniques. The Ni,Pd,Pt/Mg1-x Cex 3+O catalyst with cubic structure was synthesized using the coprecipitation method which showed good selectivity for dry reforming of methane reaction with CO2 and CH4 conversion rates of 99% and 84%, respectively, at ratio CO2:CH4, 1:1 at 900 °C. They also showed good thermal stability for the first 200h. and also, great potential for use in fuel processing. This catalyst also increased the activity & stability of DRM reaction by adding a small concentration of O2, which resulted in a combination of combustion and reforming reaction that made the overall process thermo-neutral and helped in limiting carbon formation.